2022
DOI: 10.1155/2022/4973839
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Temperature Distribution and Mechanical Properties of Friction Stir Welding of Al-Cu Joints Using Hardened H13 Steel Tools

Abstract: Friction Stir Welding (FSW) is a superior metal joining technique for joining similar and dissimilar metals. The various materials acceptable for the FSW techniques were magnesium alloys, mild steel, stainless steel, copper alloys, titanium alloys, aluminium alloys, etc. In this method, the frictional heat generated by the tool on metal workpieces was used for joining, and the workpieces were joined below the upper critical temperature. The substantial benefit of this technique is that it is capable of welding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…An analysis of temperature distribution and mechanical properties of friction stir welding of Al-Cu joints using hardened H13 steel tools was carried out. High ultimate tensile strength and impact strength were discovered to be produced at 1200 rpm tool rotational speed and 20 mm/min feed rate with the square pin profile of a hardened H13 steel tool due to the highest temperature at weld areas [12]. It has been observed that frictional temperature increases greatly when rotating speed and tilt angle increase, but adversely as welding speed increases.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of temperature distribution and mechanical properties of friction stir welding of Al-Cu joints using hardened H13 steel tools was carried out. High ultimate tensile strength and impact strength were discovered to be produced at 1200 rpm tool rotational speed and 20 mm/min feed rate with the square pin profile of a hardened H13 steel tool due to the highest temperature at weld areas [12]. It has been observed that frictional temperature increases greatly when rotating speed and tilt angle increase, but adversely as welding speed increases.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%